The experience of teaching using a game based approach: Teachers as learners, collaborators and catalysts. (May 2019) - Jarrett, Kendall; Light, Richard
This study focuses on the analysis of collective meaning associated with secondary physical education teachers' ( n = 12) experiences of teaching games using a game based approach (GBA). Participants taught in one of two different international contexts, southeast Australia or southeast England, and all had some experience of using a GBA to teach games. A phenomenographic research framework was utilised to uncover the qualitatively finite number of ways that GBA-related teaching was/can be experienced. As guided by use of a phenomenographic analysis framework, three conceptions of awareness were identified that detail the collective meaning associated with participants' experiences of teaching using a GBA, namely that of a Learner, a Collaborator and/or a Catalyst . An analysis of findings is presented with discussion focusing on what can be learnt from the different ways GBA teaching is experienced and implications for GBA teaching practice.